The FZD7‐TWIST1 axis is responsible for anoikis resistance and tumorigenesis in ovarian carcinoma - Tan, Ming; Asad, Mohammad; Heong, Valerie; Wong, Meng Kang; Tan, Tuan Zea; Ye, Jieru; Kuay, Kuee Theng; Thiery, Jean Paul; Scott, Clare; Huang, Ruby Yun‐Ju (Molecular oncology, 2019)
Frizzled family receptor 7 (FZD7), a Wnt signaling receptor, is associated with the maintenance of stem cell properties and cancer progression. FZD7 has emerged as a potential therapeutic target because it is capable of transducing both canonical and noncanonical Wnt signals. In this study, we investigated the regulatory pathway downstream of FZD7 and its functional roles. We found that FZD7 expression was crucial to the maintenance of the mesenchymal phenotype, anoikis resistance, and spheroid and tumor formation in ovarian cancer (OC). We identified TWIST1 as the crucial downstream effector of the FZD7 pathway. TWIST1, a basic helix loop helix transcription factor, is known to associate with mesenchymal and cancer stem cell phenotypes. Manipulating TWIST1 expression mimicked the functional consequences observed in the FZD7 model, and overexpression of TWIST1 partially rescued the functional phenotypes abolished by FZD7 knockdown. We further proved that FZD7 regulated TWIST1 expression through epigenetic modifications of H3K4me3 and H3K27ac at the TWIST1 proximal promoter. We also identified that the FZD7‐TWIST1 axis regulates the expression of BCL2, a gene that controls apoptosis. Identification of this FZD7‐TWIST1‐BCL2 pathway reaffirms the mechanism of anoikis resistance in OC. We subsequently showed that the FZD7‐TWIST1 axis can be targeted by using a small molecule inhibitor of porcupine, an enzyme essential for secretion and functional activation of Wnts. In conclusion, our results identified that the FZD7‐TWIST1 axis is important for tumorigenesis and anoikis resistance, and therapeutic inhibition results in cell death in OCs. Frizzled family receptor 7 (FZD7) expression maintains the mesenchymal phenotype and anchorage independence via epigenetic regulation of TWIST1. Knockdown of FZD7 results in inhibition of TWIST1 with consequent downregulation of epithelial to mesenchymal transition and BCL2 leading to anoikis and loss of tumorigenesis. Our results demonstrate that the FZD7‐TWIST1 axis is important for tumorigenesis and anoikis in ovarian cancer.